ETHNOMEDICINE OF MEDICINAL PLANTS USED BY TRADITIONAL HEALERS TO FACILITATE BONE INJURY HEALING IN WEST KALIMANTAN, INDONESIA - Fanie Indrian Mustofa; Nuning Rahmawati; Saryanto Saryanto (Balai Besar Penelitian dan Pengembangan Tanaman Obat dan Obat Tradisional, 2021)
ABSTRACT Medicinal plants have been used to facilitate bone injury healing in many communities. West Kalimantan is rich in diversity of medicinal plants and local wisdom owned by ethnic groups. As forest destruction is getting increases, it leads to the extinction of certain medicinal plant species there. Thus, it is crucial to document plant species with medicinal properties and traditional knowledge as valuable information passed down by generation. A semi-structured questionnaire was employed to interview 51 traditional healers from 28 ethnic groups that were selected by purposive sampling method. Field observation and specimen collection were carried out for botanical identification. A quantitative analysis was calculated to obtain plant proportion, Use Value (UV), Family Use Value (FUV), and Informant’s Consensus Factor (ICF). The result revealed there were 134 plant species of 53 botanical families from eight districts in West Kalimantan. Eleven species of plants reported having UV of species at least 0.10 (5 citations). Zingiber officinale was the most frequently used species to facilitate bone injury (22 citations; UV=0.43). The botanical family with the highest number of species was Rubiaceae (13 species) and the highest level of Family Use Value-FUV was Acanthaceae (0.13). The Informant Consensus Factor (ICF) for facilitating bone injury was 0.48. Most of the therapy in this study administered externally (85.07%), used leaves (66.67%), and a mixture composition from several plants (93.28%). The evaluation is critically required to support the medicinal plant’s scientific evidence in facilitating bone injury for both local and global communities. Moreover, the traditional healers need education regarding conservation issues, since most of the plants are still obtained from the wild. Keywords: medicinal plants, traditional healer, bone injury, West Kalimantan ABSTRAK Tanaman obat telah banyak dimanfaatkan untuk mengatasi cedera tulang di berbagai komunitas di Indonesia. Kalimantan Barat kaya akan keanekaragaman tumbuhan obat dan kearifan lokal yang dimiliki oleh kelompok-kelompok etnisnya. Saat ini, kerusakan hutan dan alih fungsinya mengancam kepunahan beberapa spesies tanaman obat. Oleh karena itu, penting untuk mendokumentasikan jenis tumbuhan yang berkhasiat obat dan juga pengetahuan tradisional sebagai informasi berharga yang disampaikan secara turun temurun. Studi ini melibatkan 51 pengobat tradisional dari 28 kelompok etnis yang diseleksi secara purposive sampling. Pengamatan lapangan dan pengambilan spesimen dilakukan untuk keperluan identifikasi botani. Analisis kuantitatif dilakukan untuk mendapatkan proporsi tanaman, Use Value (UV), Family Use Value (FUV), dan Informant Consensus Factor (ICF). Studi ini mengungkapkan 134 spesies tanaman obat dari 53 familia yang terdapat pada delapan kabupaten di Kalimantan Barat. Sebelas spesies tanaman dilaporkan memiliki UV spesies setidaknya 0,10 (5 sitasi). Zingiber officinale merupakan spesies yang paling sering digunakan untuk mengatasi cedera tulang (22 sitasi; UV=0,43). Familia dengan jumlah spesies tertinggi adalah Rubiaceae (13 spesies) dan nilai FUV tertinggi adalah Acanthaceae (0,13). Informant Consensus Factor (ICF) untuk memfasilitasi cedera tulang adalah 0,48. Sebagian besar terapi diberikan secara eksternal (85,07%). Penggunaan daun sebagai bahan ramuan (66,67%) dan komposisi ramuan adalah campuran dari beberapa tanaman (93,28%). Penelitian lebih lanjut sangat diperlukan untuk memberikan bukti ilmiah tanaman obat dalam mengatasi cedera tulang, baik untuk komunitas lokal maupun global. Sebagian besar tanaman masih diperoleh dari alam tanpa upaya penanaman kembali, sehingga diperlukan edukasi terkait pengetahuan konservasi bagi pengobat tradisional. Kata kunci : tumbuhan obat, pengobat tradisional, cedera tulang, Kalimantan Barat